Utilization of Learning Media in Digital Simulation Subjects - T, Nuraisyah Faradilla; Saleh, Sirajuddin; Arhas, Sitti Hardiyanti; Haerul, Haerul; Nasaruddin, Nasaruddin (Jurnal Office, 2019)
In a learning activity, the use of learning media in delivering material is very important in order to make it more effective and efficient for learning activities. This study aims to determine the use of instructional media in class X digital simulation subjects in office administration skills competency at SMK Negeri 4 Pangkep. Therefore, to achieve these objectives researchers used data collection techniques with observation, questionnaires, and documentation with a population and sample of 45 people. As well as the data processed using quantitative analysis to determine the extent to which the use of learning media in the digital simulation subjects. The results of this study indicate that the use of learning media in digital simulation subjects at SMK Negeri 4 Pangkep can be classified as good. This can be seen from the use of print media which are classified as good, the use of media reality which is classified as good and the use of electronic media which are classified as good.